"Promoting Early Presentation" intervention sustains increased breast cancer awareness in older women for three years: A randomized controlled trial. (September 2017) - Kaushal, Aradhna; Ramirez, Amanda J; Warburton, Fiona; Forster, Alice S; Linsell, Louise; Burgess, Caroline; Tucker, Lorraine; Omar, Lynne; Forbes, Lindsay JL
Objective: In a randomized controlled trial, the Promoting Early Presentation intervention increased older women's breast cancer awareness after two years. We investigated whether this increase was sustained at three years, and the effect on breast screening self-referral. Methods: We randomly allocated 867 women attending their final invited breast screening appointment to the Promoting Early Presentation intervention or usual care. We examined breast cancer awareness after three years and breast screening self-referrals after four years. Results: Women in the Promoting Early Presentation intervention arm had higher breast cancer awareness at three years than the usual care arm (odds ratio: 10.4; 95% confidence interval: 3.1 to 34.8). There were no differences in proportions self-referring for breast screening between arms, but statistical power was limited. Conclusion: The Promoting Early Presentation intervention has a sustained effect on breast cancer awareness in older women. The effect on self-referral for breast screening is unclear.